2018
DOI: 10.5530/jyp.2018.2s.12
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Transfersomal Green Tea (Camellia sinensis L. Kuntze) Leaves Extract Cream and In Vitro Penetration Study Using Franz Difussion Cell

Abstract: Introduction: Green tea is a natural ingredient that contains polyphenolic compounds in the form of catechin derivatives known as epigallocatechin gallate (EGCG). It has an antioxidant activity that is beneficial for body health. However, EGCG has a considerable molecular weight and high hydrophilicity resulting in the difficulty of skin penetration. The aim of this study was to improve EGCG penetration through the skin by using the formation of lipid nanovesicles, called transfersomes, that was formulated int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…7 ). Recent studies have shown that cilnidipine [ 124 ], diflunisal [ 125 ], sinomenine [ 126 ], green tea extract [ 127 ], pentoxifylline [ 128 ], raloxifene [ 129 ] and minoxidil [ 130 ] were all successfully formulated and delivered transdermally using transfersomes.…”
Section: Technologies For Enhancing Transdermal Deliverymentioning
confidence: 99%
“…7 ). Recent studies have shown that cilnidipine [ 124 ], diflunisal [ 125 ], sinomenine [ 126 ], green tea extract [ 127 ], pentoxifylline [ 128 ], raloxifene [ 129 ] and minoxidil [ 130 ] were all successfully formulated and delivered transdermally using transfersomes.…”
Section: Technologies For Enhancing Transdermal Deliverymentioning
confidence: 99%
“…The entrapment efficiency of transfersome increased with increasing lipid concentration (phospholipid) and decreased with increasing surfactant concentration because lower surfactant concentrations (<15%, b/b) allowed all surfactant molecules to bind to the phospholipid bilayer layer. If the concentration exceeds a certain concentration, some surfactant molecules will cause an increase in the permeability of the vesicle membrane, which can reduce the efficiency of entrapment [15,16]. Phospholipids are the main components that form vesicles.…”
Section: Entrapment Efficiencymentioning
confidence: 99%
“…Lipid degradation can also occur because of chemical degradation processes that can affect the stability of the phospholipid bilayer, such as hydrolysis and lipid oxidation. Degradation of the lipid bilayer can reduce the absorption efficiency of N-acetylcysteine so that more free N-acetylcysteine is oxidized [15].…”
Section: Accelerated Stability Testingmentioning
confidence: 99%
“…The primary catechin in green tea, epigallocatechin-3-gallate (EGCG), has been demonstrated to have ant melanogenesis, moisture retention, and skin-protecting properties. According to recent research EGCG might also help in wound healing [10]. Salicylic acid is a chemical substance that belongs to the class of aromatic hydroxy carboxylic acids (C7H6O3).…”
Section: Introductionmentioning
confidence: 99%